(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Climate change is increasingly recognized as a significant threat to mental health, particularly affecting vulnerable populations. This study investigates the impact of climate change-induced heat on mental health outcomes, focusing on stress, anxiety, and depression. Additionally, qualitative interviews provided in-depth insights into the lived experiences of individuals coping with heat-related stress. Our findings reveal a strong correlation between rising temperatures and increased instances of anxiety and depression, with marginalized communities, such as the elderly, low-income individuals, and those with pre-existing health conditions, exhibiting heightened vulnerability. The physiological strain of heat, compounded by socioeconomic and environmental factors, exacerbates mental health issues, leading to a cyclical pattern of distress. The study highlights the necessity for targeted public health interventions, emphasizing the development of adaptive strategies to mitigate the mental health impacts of heat. Furthermore, integrating mental health support into climate adaptation strategies is crucial for building resilience and ensuring that vulnerable populations receive the necessary resources to manage both the psychological and physical impacts of heatwaves By addressing the intersection of environmental and mental health crises, we advocate for comprehensive support systems to enhance resilience in vulnerable populations. This study contributes to the growing body of evidence on the far-reaching effects of climate change, advocating for proactive measures to safeguard mental well-being in an era of escalating environmental challenges.